Electrical principles and practices : workbook - 422445 Mazur, Glen A.; Zurlis, Peter A. (Homewood, Illinois : American Technical Pub., 2007)
With : Electrical principles and practices (TK146 M39 2007 f), Electrical principles and practices : resource guide (TK146 M37 2007 f), Test Development software featuring Exam view (CP 015375 )